Kompetensi Pustakawan Pasca Pandemi Covid-19 di Perpustakaan FKKMK Universitas Gadjah Mada - Mustar, Maniso; Setyo Devi, Katrin (Perpustakaan Universitas Gadjah Mada, 2024)
The professionalism and competence of the librarians of the Faculty of Medicine, Public Health and Nursing, Gadjah Mada University (FKKMK UGM) and high-quality library services are major concerns during the COVID-19 pandemic. This study aims to analyze competency improvement and factors that influence librarian competence and efforts that must be made to maintain and improve librarian competence in the UGM FKKMK library after the Covid-19 pandemic. This research was conducted qualitatively and data was collected through interviews and observations from May 15 to 30 May 2023 with seven (7) Librarians of FKKMK UGM. The results showed that the key factors influencing the competence and professionalism of librarians at the Gadjah Mada University FKKMK library after the Covid-19 pandemic were competence, motivation, management support, work environment, and involvement in professional training and development. Efforts are being made to maintain and improve it, including increasing the competence and skills of librarians through professional training and development, providing adequate management support, encouraging the involvement of librarians in professional and organizational activities, and creating a conducive work environment. Factors such as competence, motivation, management support, work environment, and involvement in training and professional development play an important role in increasing the professionalism of librarians. Therefore, there needs to be action taken to maintain and improve the professionalism of librarians through professional training and development, management support, involvement in professional and organizational activities, and creating a conducive work environment.